Intramedullary abscess extending to the cauda equina with paraplegia in a 6-month-old infant - Rajput, Dinesh K.; Srivastav, Arun K.; Tiwari, Ravi K.; Kawal, Priyanka; Kumar, Raj; Mahapatra, Ashok K. (Journal of Pediatric Neurology, 2011)
Intramedullary spinal cord abscesses are uncommon lesions. Forty percent of all such abscesses occur before 20 yr of age. Patients with acute onset of symptoms and signs have a graver prognosis. This generally occurs in the setting of systemic bacteremia. A case of large intramedullary spinal cord abscess extending up to the terminal spinal canal in a 6-month-old male baby who developed flaccid paraplegia without an evidence of systemic infection or septicemia or anatomical defect is reported. The possibility of infection of an epidermoid in such cases cannot ruled out.
Keywords: Intramedullary; infections; abscess; lesions